2018
DOI: 10.32648/2577-9516/2/1/004
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of Stress and Coping among Nursing Students in the College of Nursing at University of Hail, Saudi Arabia

Abstract: Background: Faced with a multiple roles from the demands of classroom and clinical area, nursing students are predisposed to stressful experience. As panacea thereof, an implementation of applicable coping intermediations to assist in the management of stress in nursing students is a pressing need. Methods: This research employed a cross-sectional analytical design using regression analysis in probing the association of the demographic variables affecting the perceived stress and coping among nursing student… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 34 publications
1
5
1
Order By: Relevance
“…As has been shown, the stress experienced and remedial activities undertaken by students modify their quality of life and health. In the current study, the average results of perceived stress on the PSS-10 scale for nursing students from Poland, Spain and Slovakia ranged from 18.55 ± 6.07 to 18.66 ± 4.70 and were slightly lower than in the cross-sectional research conducted at the University of Dammam in Saudi Arabia among nursing students (20.52 ± 7.59) [35]. Research conducted by various authors shows that the intensity of stress in other fields of study is at a similar level or significantly higher than in own research.…”
Section: Discussioncontrasting
confidence: 71%
See 1 more Smart Citation
“…As has been shown, the stress experienced and remedial activities undertaken by students modify their quality of life and health. In the current study, the average results of perceived stress on the PSS-10 scale for nursing students from Poland, Spain and Slovakia ranged from 18.55 ± 6.07 to 18.66 ± 4.70 and were slightly lower than in the cross-sectional research conducted at the University of Dammam in Saudi Arabia among nursing students (20.52 ± 7.59) [35]. Research conducted by various authors shows that the intensity of stress in other fields of study is at a similar level or significantly higher than in own research.…”
Section: Discussioncontrasting
confidence: 71%
“…A much more favourable situation among students was recorded in a study conducted by Albaqawi in Saudi Arabia. It was found that only 22.5% of the respondents experienced high levels of stress [35]. In turn, Labrague et al also reviewed 11 items of research literature describing the perception of stress among nursing students from Saudi Arabia.…”
Section: Discussionmentioning
confidence: 99%
“…Stress among nurses can have a negative impact on their mental health, which can lead to several conditions such as burnout, depression, and lack of compassion and empathy (Khamisa et al, 2015). Stress is defined as an alteration in the homeostasis of a person due to various factors that may affect the physical, mental, emotional, and behavioral aspects of a person (Albaqawi, 2018;Chipas et al, 2012). The presence of stress in a nursing environment poses a health hazard resulting in poor clinical judgment and compromised patient safety (Hiler et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Different facets have been addressed. Thus, we distinguish the stress factor and determinant studies [2], [3], [4], [5], [6], [7]. Others have been interested to the stress impact [8], [9], [10], [11], [12] and the coping stress strategies [2], [13], [14].…”
Section: Introductionmentioning
confidence: 99%
“…Thus, we distinguish the stress factor and determinant studies [2], [3], [4], [5], [6], [7]. Others have been interested to the stress impact [8], [9], [10], [11], [12] and the coping stress strategies [2], [13], [14]. Similarly, some studies have examined the stress levels [15], [16], [17], [18], [19], [20], [21], [22].…”
Section: Introductionmentioning
confidence: 99%